Managing Credit Risk in Microfinance : Challenges in the Wake of the Arab Spring - Leonard, Matt (International Finance Corporation, Washington, DC, 2015)
Enda Inter-Arabe (ENDA), a market-leading microfinance institution (MFI) in Tunisia, was one of the first MFIs affected by a repayment crisis linked to the so-called Arab Spring. However, rather than spiral out of control, ENDA took quick steps to limit the damage while demonstrating an unwavering commitment to its clients. Today, International Finance Corporation (IFC) is helping ENDA remain at the vanguard of regional MFIs through the adoption of advanced risk-management practices. This report highlights the lessons learned from the crisis, explores the nuances of effective credit risk management, and shows how MFIs like ENDA can remain ahead of the curve in the years to come.